2021
DOI: 10.14421/jpsi.v9i1.2137
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experience Dan Deliberate Self Harm Pada Remaja Di Indonesia

Abstract: Self-injurious behavior or acts of self-harm that are commonly found in adolescents are form of channeling negative emotions to deal with emotional pain. One reason for this pain was exposure to unpleasant experiences called adverse childhood experiences. This study aims to explore the detrimental effect of experience on self-harm in adolescents. This study used two measuring instruments, the Deliberate Self-Harm Inventory (DSHI) was used to measure DSH and Adverse Childhood Experience Quesionnaire (ACE.Q) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
4
0
4
Order By: Relevance
“…Di Indonesia, peneliti terkait dengan kecemasan sosial hanya fokus pada aspek regulasi diri (Elfariani & Anastasya, 2023), aspek efikasi diri (Suryaningrum, 2016), aspek pola asuh (Rachmawaty, 2015). Sedangkan yang meneliti ACE sendiri di Indonesia fokus mengungkap internalizing problem dan externalizing problem (Bakhtiar et al, 2023), deliberate selfharm (Paramita et al, 2020), self-criticism (Purnomo & Dewi, 2023) oleh karenanya dengan memperbaiki berbagai keterbatasan yang ada, menjadi peluang untuk diteliti lebih lanjut agar konsistensi temuannya dapat diketahui pada populasi Indonesia.…”
Section: Diskusiunclassified
“…Di Indonesia, peneliti terkait dengan kecemasan sosial hanya fokus pada aspek regulasi diri (Elfariani & Anastasya, 2023), aspek efikasi diri (Suryaningrum, 2016), aspek pola asuh (Rachmawaty, 2015). Sedangkan yang meneliti ACE sendiri di Indonesia fokus mengungkap internalizing problem dan externalizing problem (Bakhtiar et al, 2023), deliberate selfharm (Paramita et al, 2020), self-criticism (Purnomo & Dewi, 2023) oleh karenanya dengan memperbaiki berbagai keterbatasan yang ada, menjadi peluang untuk diteliti lebih lanjut agar konsistensi temuannya dapat diketahui pada populasi Indonesia.…”
Section: Diskusiunclassified
“…This study utilized three research instruments, with the first part focusing on collecting demographic data from the respondents. The second part consists of the Adverse Childhood Experiences Questionnaire (ACEs.Q) and the third part includes the Deliberate Self-Harm Inventory (DSHI) questionnaire, which has been translated and adapted into Indonesian (Paramita et al, 2021). The ACE questionnaire consists of 28 questions.…”
Section: Instrumentmentioning
confidence: 99%
“…Multiple studies conducted in many countries have demonstrated a significant association between deliberate self harm with adverse childhood experiences among teenagers (Brown & Witt, 2019;Cleare et al, 2019;Paramita et al, 2021;Wan et al, 2015). Adverse Childhood Experiences (ACEs) refer to traumatic events, occur between the ages of 0 and 17, that leave lasting imprints on a kid's subconscious and have an impact on physical, emotional, and mental health (Adverse Childhood Experiences (ACEs), 2023; Marryat & Frank, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bentuk penyaluran self-harm yaitu mencakar dan melukai tubuh dengan sengaja tanpa niat melakukan bunuh diri. Perilaku tersebut juga dilakukan dengan menyilet bagian tubuhnya (contohnya, pergelangan tangan) (Paramita., Faradiba., & Mustofa, 2020). Menurut penelitian Wahyuni, Nauli, dan Jumaini (2020) didapatkan hasil 21,4% dari 393 mahasiswa mengalami perilaku melukai diri sendiri (self-harm) sebagai bentuk pelampiasan masalah kesehatan mental mereka.…”
Section: Jurnal Nurseunclassified